Erratum: JOÃO F. SANTOS-NETO, SAYMON M. PAIXÃO & MARCUS V. DOMINGUES (2024) Two new species of Monopisthocotyla (Dactylogyridea: Dactylogyridae) parasitizing the nasal cavities of Bryconops melanurus (Characiformes: Iguanodectidae) from coastal drainages of the Eastern Amazon, Brazil. Zootaxa, 5410 (2): 222–238. - Santosneto, João F.; Paixão, Saymon M.; Domingues, Marcus V. (Zootaxa, 2024)
N/A